2019
DOI: 10.1001/jamanetworkopen.2019.17254
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of, Risk Factors for, and Mortality Associated With Severe Acute Kidney Injury After Gunshot Wound

Abstract: IMPORTANCE Acute kidney injury increases the risk of mortality in hospitalized patients. However, incidence of severe acute kidney injury (SAKI) and its association with mortality in civilians with gunshot wounds (GSWs) is not known. OBJECTIVE To determine the incidence of and risk factors associated with SAKI and acute kidney injury requiring dialysis (AKI-D) after GSWs and the association of SAKI and AKI-D with mortality among civilians in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Age was an independent risk factor for the initiation, development, and adverse outcome of AKI 27 , 28 . This study represented the analysis of AKI among hospitalized elderly patients in China.…”
Section: Discussionmentioning
confidence: 96%
“…Age was an independent risk factor for the initiation, development, and adverse outcome of AKI 27 , 28 . This study represented the analysis of AKI among hospitalized elderly patients in China.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple studies have revealed that AKI is common and associated with poor clinical outcomes in EDs [ 2 4 ], emergency hospitalization [ 5 ], hospital wards [ 6 ], and intensive care units (ICUs) [ 7 9 ]. AKI development is also associated with a higher mortality rate in various clinical contexts, including sepsis [ 10 12 ], cardiogenic shock [ 13 ], chest pain [ 14 ], gunshot wound [ 15 ], emergent laparotomy [ 16 ], and out-of-hospital cardiac arrest [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute Kidney Injury (AKI) is characterized by a sudden decrease in the renal function 1 . It represents a severe health condition worldwide, as it exerts several impacts on survival and increases the risk of progression to Chronic Kidney Disease (CKD) 2 .…”
Section: Introductionmentioning
confidence: 99%